An overview of conventional and emerging techniques of roasting: Effect on food bioactive signatures. (30th June 2021) - Sruthi, N.U.; Premjit, Yashaswini; Pandiselvam, R.; Kothakota, Anjineyulu; Ramesh, S.V.
Highlights: A synopsis of heat and mass transfer mechanism during roasting. Overview of conventional and emerging roasting methods. Novel techniques ensure uniform and efficient roasting with superior control. A critical appraisal of the effect of roasting on different food matrix components. Abstract: Roasting is a food processing technique that employs the principle of heating to cook the product evenly and enhance the digestibility, palatability and sensory aspects of foods with desirable structural modifications of the food matrix. With the burgeoning demand for fortified roasted products along with the concern for food hygiene and the effects of harmful compounds, novel roasting techniques, and equipment to overcome the limitations of conventional operations are indispensable. Roasting techniques employing microwave, infrared hot-air, superheated steam, Revtech roaster, and Forced Convection Continuous Tumble (FCCT) roasting have been figuratively emerging to prominence for effectively roasting different foods without compromising the nutritional quality. The present review critically appraises various conventional and emerging roasting techniques, their advantages and limitations, and their effect on different food matrix components, functional properties, structural attributes, and sensory aspects for a wide range of products. It was seen that thermal processing at high temperatures for increased durations affected both the physicochemical and structural properties of food. Nevertheless, novel techniques caused minimum destructive impacts as compared to the traditional processes. However, further studies applying novel roasting techniques with a wide range of operating conditions on different types of products are crucial to establish the potential of these techniques in obtaining safe, quality foods.